Automatic Evaluation of Descriptive Answer Using Pattern Matching Algorithm - Nikam, Pranali; Shinde, Mayuri; Mahajan, Rajashree; Kadam, Shashikala (International Journal of Computer Sciences and Engineering, 2015)
Automation of descriptive answer evaluation process would be helpful for various universities and academic institution to efficiently handle the assessment of exam answer sheets of students. Our objective is to design an algorithm for the automatic evaluation of multiple sentence descriptive answer. This paper represents an approach to check the degree of learning of the student, by evaluating their descriptive exam answer sheets. By representing the descriptive answer in the form of graph and comparing it with standard answer are the key steps in our approach. In this approach we use pattern matching algorithm for evaluation of answer. .assumption is no grammar checking.